Parque estadual serra de caldas novas (pescan): ecoturismo, compreensões de meio ambiente e práticas ambientais dos visitantes - (:unkn) unknown (Universidade Estadual de Goiás, 2015)
The Conservation Unities (CU) have been considered as tools able to promote the environmental protection, and they also enable the visitors contact with the protected environment, arousing them the interest for environmental issues. The present study has the purpose of investigate the public use of the Serra de Caldas Novas State Park (PESCaN), located in the municipalities of Goiás, Caldas Novas and Rio Quente, with the general goal of: “understand the ecotourism at PESCaN, and know and analyze the understandings of the environment and of the Environmental Education (EE) that the visitors from the UC have, and also the environmental actions they perform”. The specific goals included: i. Get to know and analyze the goals that take the visitors at PESCaN to look for it at their free time; ii. Interpret the rate of significance and knowledge of the visitors about the issues related to the environment; iii. Analyze the understanding of the EE theme of the visitors; iv. Investigate and analyze the actions in favor of the environment practiced by the visitors, according to their speech; v. Investigate whether the environmental understanding of the visitors change after the tour; and vi. Analyze the way the ecotourism activities are being developed at PESCaN. The methodology was structured through bibliographic research and field research. The former is based on the authors‟ theories such as: Wearing and Neil (2001); Costa (2002); Kinker (2002); Takahashi and Milano (2002); Barros (2003); Pires (2004); Jacobi et al (2004); Magalhães (2005); Dutra et al (2008); Ramos and Oliveira (2008); Freitas (2009); Medeiros and Araújo (2011); Soibert and Oliveira (2011); Simonetti and Nascimento (2012); Muhle (2012); among others, who discuss subjects related to the themes of the environment, the tourism and the ecotourism, and also related to the use and conservation of protected areas, and the study of understanding and characteristics of visitors. The latter, based on the conducted investigation through the survey applied to the visitors, when they arrived and left PESCaN, as a way to analyze their socioeconomic characteristics, the environmental understanding, their environmental practices, and whether the park changes these understandings after the tour. In addition, 273 visitors were interviewed, and the results showed satisfactory rates for PESCaN and for the treatment of environmental issues: more than half of the interviewed look for the unity to perform scientific researches, school activities or technical visitation; about one third go to the park to know the unity, its attractions and the Cerrado; nearly 70% of the interviewed have the habit to visit other CU. The environment is considered as a system of integration and interaction between man and nature for nearly 85% of the visitors, a result held in the entrance and in the exit of the park; a few more than 90% act in favor of the environment, mainly when it is related to recycling/ selective collection, saving water and projects of environmental awareness. The interest to participate in any EE program after the tour in the park was expressed by 90% of the visitors, mainly related to a program connected to the environmental conservation or with students and/or society awareness. The unity was evaluated with the grade from 9,0 to 10,0 for almost 63% of the interviewed; nearly everyone would visit the park again and they would suggest the visit to friends and relatives. The existence of an active Advisory Council and the definition of Buffer Zone are favorable points for the CU management. The lack of regulation of the Management Plan, the low use of the park structure and the little involvement of the employees with the activities are showed as unfavorable points.
Keywords: Unidade de conservação; Educação ambiental; Ecoturismo e práticas ambientais; Proteção ambiental; Visitação pública; Conservation unity and; Environmental education; Ecotourism and environmental practices; Environmental protection; Public visitation; CIENCIAS BIOLOGICAS